2018
DOI: 10.1038/s41598-018-26407-3
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Alginate-Gelatin Bioink Properties by Varying Solvent and Their Impact on Stem Cell Behavior

Abstract: Bioink optimization is considered as one of main challenges in cell-laden 3D bioprinting. Alginate-Gelatin (Alg-Gel) hydrogel have been extensively used as bioink. However, its properties could be influenced by various parameters, and little is known about the evidence featuring the impact of solvent. Here we investigated four Alg-Gel bioink by varying solvent ionic strength (named B-1, B-2, B-3 and B-4). Mechanical properties and printability of bioink samples and their impacts on behaviors of encapsulated ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
122
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 27 publications
0
122
0
1
Order By: Relevance
“…Human corneal epithelial cells (HCECs) were bioprinted in collagen–gelatin–alginate composite hydrogels, and the scaffolds were exposed to sodium citrate, yielding controlled degradation, which in turn resulted in high cell viability (>90%), proliferation, and cytokeratin 3 (CK3) expression . Alginate–gelatin bioinks can also be engineered by tailoring the ionic strength . The storage and loss moduli of bioprinted constructs decreased using 1× (165 mM) and 2× (328 mM) phosphate‐buffered saline (PBS), resulting in mechanically weak, fast‐swelling, and unstable scaffolds, incapable of hosting epidermal stem cells.…”
Section: Gelatin–polysaccharides Composites In Cell Culture and Tissumentioning
confidence: 99%
See 3 more Smart Citations
“…Human corneal epithelial cells (HCECs) were bioprinted in collagen–gelatin–alginate composite hydrogels, and the scaffolds were exposed to sodium citrate, yielding controlled degradation, which in turn resulted in high cell viability (>90%), proliferation, and cytokeratin 3 (CK3) expression . Alginate–gelatin bioinks can also be engineered by tailoring the ionic strength . The storage and loss moduli of bioprinted constructs decreased using 1× (165 mM) and 2× (328 mM) phosphate‐buffered saline (PBS), resulting in mechanically weak, fast‐swelling, and unstable scaffolds, incapable of hosting epidermal stem cells.…”
Section: Gelatin–polysaccharides Composites In Cell Culture and Tissumentioning
confidence: 99%
“…Similarly, without PBS, the cells remained isolated from each other and were not able to proliferate. The optimum concentration of PBS (82 mM, 0.5×) resulted in improved cell function in terms of viability, proliferation, glandular morphology, and differentiation to epithelium and sweat glands, while providing a decent printability of epidermal stem cell‐laden constructs, setting the stage for the regeneration of sweat glands …”
Section: Gelatin–polysaccharides Composites In Cell Culture and Tissumentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, properties of bioink can be influenced by various parameters, which significantly impact cell behaviour and tissue formation within printed constructs. In our previous work, we modulated bioink properties by varying the solvent ionic strength of Alg‐Gel hydrogel and indicated that this modulation had a profound effect on stem cell behaviours in 3D bioprinting …”
Section: Bioinkmentioning
confidence: 99%